A new HLA‐DQB1 allele, HLA‐DQB1*04:62, identified in a Chinese family. (25th March 2021) - Ai, Xiaofei; Wang, Jiying; Zhang, Yan; Li, Qinghua; Wang, Xiaojing
Abstract : HLA‐DQB1*04:62 differs from HLA‐DQB1*04:01:01:01 by a single nucleotide in exon 3 (433A‐>G, N113D).